Raw Material Logistics Performance Measurement Using OMAX Method - Winoto Hadi; Vivian Karim Ladesi; Nur Azisah; Lintang Prima; Rajendran Narayanasamy (Politeknik APP Jakarta, 2026)
The Fast-Moving Consumer Goods [FMCG] industry plays a strategic role in the Indonesian economy, where raw material logistics management remains a key challenge directly impacting production efficiency and competitiveness. This study analyzes the logistics performance of raw material suppliers at an Instant Noodle Company to identify performance patterns and their impact on operational efficiency using the Objective Matrix (OMAX) method across three main categories: seasoning, seasoning and vegetable oil, and packaging over one year. The results reveal significant variations in supplier performance, with the seasoning category showing substantial improvements in Cikampek and Semarang facilities correlating with increased production, while Surabaya experienced a notable decline. The seasoning and vegetable oil category demonstrated stable performance despite minor production fluctuations, whereas the packaging category revealed consistent performance deterioration among key suppliers, negatively affecting production capacity. The findings indicate that supplier performance directly influences logistics efficiency and production capacity. This study recommends supplier development programs, performance monitoring systems, and supplier portfolio diversification to enhance consistency and competitiveness in the FMCG sector.